Pengembangan Rencana Pelaksanaan Pembelajaran (RPP) Menggunakan Model Pembelajaran Kooperatif tipe Number Head Together (NHT) Pada Pembelajaran Tematik Di Kelas V SD Negeri Kota Bengkulu - Randi Elsa Putra; Wurjinem Wurjinem; Hasnawati Hasnawati (Universitas Bengkulu, 2020)
This study aims to develop a Learning Implementation Plan (RPP) using the Number Head Together (NHT) cooperative model in class V of public elementary schools that can be used as a reference for teachers in implementing classroom learning. This research is a Research and Development (R&D) research by modifying the 4-D model by Thiagarajan and Sammel which includes Define, Design, Develop, and Disseminate. This research was only carried out until the third stage, namely Develop (Development). Validation was carried out by 3 experts who each validated the Design, Material, and Language. The lesson plans developed were given scores and responses by 8 teachers to assess the products developed from the presentation and material aspects. The research subjects were teachers of class V SD Negeri Bengkulu City. The instrument used in the form of a validation sheet to obtain input in the form of assessments, notes, criticisms and suggestions for the initial draft lesson plans and teacher response questionnaires to collect data about teacher responses to the lesson plans that have been developed. The data analysis technique used qualitative descriptive analysis and descriptive statistics, namely expert validation data analysis and teacher response data analysis. This research produces RPP cooperative model type Number Head Together (NHT) with the assessment of 3 experts with an average of 90.41 with a very good category and teacher responses of 91.71 with very good category as the final product of development. Keywords: Development, RPP, Cooperative Type Number Head Together (NHT), Thematicc